بنیاتی ناونیشان لە ڕۆمانەکانی (کاروان عومەر کاکەسوور)دا - عیسا, پ.ی.د. هاوژین صلیوه‌; نوری, م.ی. شوان عثمان (Sulaimani Journal for Humanities, 2023)
The title in modern literary has a good concern and as a gate, draws readers attention. It depends on the novelists abilities, how he or she compose the title and the complicated plots. How much he or she has the ability to draw readers attention through the title of the text. (Karwan Kakaswr) as a prominent voice in narration world, has treated carefully with these fundamental structurs of the text. The titles of his novels make the readers to have lots of look and pause. And that shows the ability of the novelist in composing and choosing the title. The titles of his novels carry lots of codes and symbols, that make the reader goes deep in to the text to search for the secret symbols, that are concentrated in the title.
Keywords: دەلالەتی ناونیشان ژەهر یادەوەریی ڕێبەن بووکەڵەکان ملپێچ